Assessment of the protective and ameliorative impact of quercetin nanoparticles against neuronal damage induced in the hippocampus by acrolein - Samia M. Sanad; Safaa E. Nassar; Reham Farouk (Beni-Suef University Journal of Basic and Applied Sciences, 2024)
Abstract Background The most frequent kind of dementia in the senior population is Alzheimer's disease (AD). Antioxidant quercetin has a low bioavailability. The bioavailability of quercetin nanoparticles was demonstrated to be higher. Acrolein is thought to be the strongest unsaturated aldehyde. Acrolein contributes to the propagation of oxidative damage and thus the aetiology of AD. This study aimed to investigate histopathological and ultrastructural changes that may arise in the hippocampus following acrolein treatment. Quercetin nanoparticles' ameliorative and protective effects on acrolein-induced neurotoxicity and oxidative stress were assessed. Results We successfully synthesised quercetin nanoparticles with uniform size distributions and particle diameters in the range of 3.63–4.57 nm using transmission electron microscopy (TEM) and 3.7 nm using dynamic light scattering (DLS). Administration of acrolein was associated with histopathological alterations in the hippocampal structure, such as increased apoptotic neurones, dystrophic changes, neuronophagia, and atrophic ischaemia in cells, as well as marked damage to the ultrastructure of the hippocampus, which was obvious in shrunken pyramidal neurones with pyknotic nuclei and completely degenerated chromatin material, as well as in damaged astrocytes and microglial cells. Treatment with quercetin nanoparticles has been found to protect against and ameliorate the toxic effects and oxidative stress induced by acrolein in the hippocampus. Conclusions This could pave the way for additional research in nanomedicine and a new line of therapeutic intervention in AD using nanoparticles such as quercetin nanoparticles.